Penerapan SPO Pelaksanaan Asuhan Keperawatan di Ruang Sub Instalasi Rawat Inap X Rumah Sakit Militer Jakarta: Pilot Study - Nilasari, putri; Hariyati, Rr Tutik Sri; Anisah, Siti (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Holistic nursing care is care that should be given by a nurse. However, it is known that nurses have missed oneof several activities in nursing care. This study aims to describe the implementation of nursing care in theinpatient ward A Military Hospital in Jakarta. The method used is a pilot study through 23 medical recorddocuments, observations, and interviews with patients and families. The stage begins with the initialassessment, fishbone analysis, PDSA (Plan, Do, Study, Action), implementation and evaluation. Theimplementation is in the form of SPO drafting and form optimization, outreach, mentoring, and roleplay videos.The results of the study showed there was improvement in the process of evaluating nursing care reaching78.26%. While nursing actions showed a significant increase in meeting bathing needs reaching 75%, ROMreaching 70%, sitting in a wheelchair, and dangling reaching 100%. Success is influenced by materialresources in the form of SPO and support and the role of the nurse manager. The recommendations of thisstudy can be the basis for optimizing the implementation of nursing care in hospitals.